PENGARUH KEPEMILIKAN INSTITUSIONAL, GROWTH OPPORTUNITIES DAN PROFITABILITAS TERHADAP KONSERVATISME AKUNTANSI PADA PERUSAHAAN BUMN PERIODE 2017 – 2020 - Ceacilia Srimindarti; Alifvina Larasati (SIMAK, 2021)
This research aims to examine the influence of institutional ownership, growth opportunities, and profitability on accounting conservatism on state-owned companies listed on the Indonesia Stock Exchange in the period 2017 – 2020. The sampling method used is purposive sampling, with the amount of data processed as many as 49 companies from 100 owned companies. The method of data analysis use multiple linear regression. The results showed that institutional ownership had a significant negative effect and profitability had a significant positive effect on accounting conservatism. While growth opportunities have no effect on accounting conservatism.